DAMPAK KEBERADAAN PT. CARIDEA JAYA LESTARI TERHADAP PENDAPATAN MASYARAKAT DI KECAMATAN UTAN KABUPATEN SUMBAWA - Sudiyarti, Nining; Irwansyah, I (Jurnal Ekonomi & Bisnis, 2025)
This study aims to determine the differences in community income before and after the existence of a shrimp farming company in Motong Village, Utan Sub-District, Sumbawa District. The type of this study was comparative study which aims to compare the level of community income before and after the existence of the shrimp farming company. The type of data used in this study was quantitative data obtained directly from primary sources using interview techniques. The primary data source for this study was all 34 employees of PT. Caridea Jaya Lestari. The data analysis technique used the two-average difference test technique, including the paired samples statistics test, paired samples correlations test, and paired samples t-test. The results of study showed that there is a positive and significant difference in the level of income of traders before and after the existence of Genang Genis Park Sumbawa Besar. Traders' income experienced a significant increase after the existence of Genang Genis Park Sumbawa Besar compared to previous income. Thus, it can be stated that the existence of Genang Genis Park Sumbawa Besar had a big impact on increasing the income earned by traders in Sumbawa Besar City.